CROTALARIA PROSTRATA VAR. LEVIS HAINES (LEGUMINOSAE): A POORLY KNOWN SPECIES REDISCOVERED, REDESCRIBED AND ENDEMIC FROM THE NORTHERN WESTERN GHATS, INDIA - DHATCHANAMOORTHY, NARAYANASAMY; SEBASTIAN SOOSAIRAJ, PRAKASAM RAJA,; ANBARASHAN, MUNISAMY (Current Botany, 2018)
During a medicinal plant survey in Amba MPCA, Raigarh District of Maharashtra, a rare and endemic species of Crotalaria, Crotalaria prostrata var. levis, (Fabaceae) were rediscovered after type specimens author collected from Amba MPCA in Maharashtra after 94 years.